The Urgency of Strengthening the Rights and Participation of Indigenous Peoples in Realizing Sustainable Management of Customary Forest - Annisa Indah Nuari; Sapto Hermawan (Kanun Jurnal Ilmu Hukum, 2021)
This article aims to analyze the urgency of strengthening the rights and participation of indigenous peoples in customary forest management in Indonesia. Law No. 41/1999 on Forestry, which is still centralized in nature, has limited the rights and roles of indigenous peoples in managing their customary forests. The regulation regarding customary forest in the Forestry Law is inconsistent with protecting ecosystem carrying capacity and democratic decentralization. This article was prepared using a normative legal research methodology in which a statutory and conceptual approach is used. Then, secondary sources of legal material were analyzed and qualified to be narrowed down to answer existing juridical problems. The results show that the rights and roles of indigenous peoples in managing their customary forests are still minimal. Customary forest management centered on the central government and prioritized a sectoral approach can have implications for exploitation that ignores the interests of conserva-tion and sustainability of customary forest natural resources.